The Mechanisms of Guaranteeing the Right to Clean Air in Iran and International Documents - Fatemeh Hamidi; Maryam Afshari; Ali Mashhadi (محیط زیست و توسعه فرابخشی)
Introduction: Air pollution is a major global environmental problem that has various adverse effects on health and the environment. Countries have come to the conclusion that the fight against this problem will only be possible through international cooperation. Therefore, taking measures to reform the existing structures based on scientific principles and applying the laws and experiences of other countries in the world to deal with air pollution are among the main priorities. The distinction of this research is to investigate the role of international guarantees and documents and Iranian laws in dealing with air pollution, so this research seeks to bridge the gap between domestic laws and documents in comparison with international laws.Materials and Methods: The present study is in the group of applied research in terms of objectives and nature, and an analytical-descriptive method has been used in its conduct. First, these documents and laws were studied in the form of a library, then according to the questions and conceptual framework, the documents and laws in the national and international system were analyzed, and finally the documents and laws were implemented. To investigate the hypotheses, dialectics, which is one of the methods of scientific cognition (research), was used.Results: In the environmental sector, the law of the Fifth Five-Year Plan is not sufficient and does not include comprehensive and long-term plans to achieve sustainable and appropriate development. The municipal law approved in 1955 has also not been able to play a significant role in the realization of the guarantee of the human right to clean air due to the lack of executive guarantees and up-to-dateness. The Environmental Protection and Improvement Act of 1974 also needs to be revised and amended due to the objective conditions of the post-revolutionary society and the flaws and inadequacies of the regulations. Although the penalty of fine in the Clean Air Law has increased in terms of amount compared to the previous law, unfortunately, it has less power than these perpetrators in the case of factories and legal entities that have more income. Regarding the performance of the Clean Air Act, it can be stated that out of the 56 articles stipulated in the Clean Air Law and its technical regulations, the implementation of 22 articles has been estimated to be poor, 17 to moderate, and 17 to be good. International instruments also lack a clear guarantee of implementation, and the mechanism provided for in the conventions seems to be very simple and inefficient.Discussion: The laws and approvals related to air pollution have not been properly implemented, and this issue is more noticeable in the case of the Clean Air Act. The most important reasons for the lack of law enforcement are lack of financial resources, lack of priority to the issue of air pollution, lack of adequate and effective supervision, inconsistency between the executive agencies and island operations, personal interpretation of the law's texts, and finally, the flaws in the text of the law. According to the results of the present study, it can be acknowledged that in Iran, as a developing country, the issue of guaranteeing the right to clean air and its implementation mechanisms has not yet found its real place in the legal system. International instruments also lack a specific guarantee of performance such as reciprocity or specific contractual mechanisms. Due to the negative effects of air pollution on the health of citizens and the country's economy, urgent action to untie the existing knots over the implementation of the Clean Air Act is necessary and there must be a serious will in this regard.